Laying the foundations for multichannel marketing through CRM strategy - Payne, Adrian (Henry Stewart Talks, 2008)
Positioning multichannel marketing within CRM strategy, The key processes in CRM strategy, The CRM strategy framework, Multichannel marketing and customer experience, Lessons from best practice exemplars
Archived at 2022/03/17